How Does Service Innovation Enhance Financial Performance in Manufacturing Enterprises?: Evidence from China - Shuie Sun; Zhenfeng Cheng (Discrete Dynamics in Nature and Society)
The precise relationship between service innovation and financial outcomes in this context remains ambiguous. This study examines the extent to which service innovation contributes to financial outcomes, analyzing data from 512 manufacturing companies across China from 1993 to 2017, sourced from the CSMAR database. Utilizing OLS regression and fixed effects model method, we identify a positive nonlinear correlation between service innovation and financial performance, highlighting a “service dilemma” that varies between state-owned and private enterprises, which follows a “saddle-type” pattern. In addition, the impact of service innovation shows considerable variation across different industries. This research provides critical insights into optimizing financial performance through strategic service innovation across various types of enterprises and industries. It underscores the importance of tailored industrial strategies and equitable competition in enhancing service innovation. The study’s extensive sample size and its focus on the heterogeneity among enterprise types and industries mark its key contributions to understand service innovation’s role in financial performance.